TEACHING OLDER PRESCHOOL CHILDREN IN THE PROCESS OF EDUCATIONAL ACTIVITIES - Ashirbayeva A.N, Ashirbayeva A.N (Журнал иностранных языков и лингвистики, 2021)
From the moment of birth, the child is mastering the world around him. Nature itself has taken care of this. Through its sensations, the child’s brain receives knowledge and helps him adapt in the most complex world of adults. But for this process to be more effective, older preschool children need to be taught the techniques of educational activities, therefore, children need an individual approach, increased attention, help from educators and parents, and timely, qualified, systematic assistance.